2017
DOI: 10.1039/c6en00440g
|View full text |Cite
|
Sign up to set email alerts
|

Metal uptake and distribution in the zebrafish (Danio rerio) embryo: differences between nanoparticles and metal ions

Abstract: Quantitative data on nanoparticle and cation uptake are compared in a compartment-specific way and distinct differences between metals were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Since ROS were highly localized in zebrafish treated with 1 , we explored methods for determining drug localization in vivo . Laser ablation coupled to inductively coupled plasma mass spectrometry (LA-ICP-MS), 50 nanoscale secondary ion mass spectrometry (nanoSIMS) imaging, 51 and electron microscopy 52 have been explored for the detection of metal ions and nanoparticles in zebrafish. Confocal microscopy and fluorescent complex 6 provide an alternative strategy, which utilizes the transparent properties of zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Since ROS were highly localized in zebrafish treated with 1 , we explored methods for determining drug localization in vivo . Laser ablation coupled to inductively coupled plasma mass spectrometry (LA-ICP-MS), 50 nanoscale secondary ion mass spectrometry (nanoSIMS) imaging, 51 and electron microscopy 52 have been explored for the detection of metal ions and nanoparticles in zebrafish. Confocal microscopy and fluorescent complex 6 provide an alternative strategy, which utilizes the transparent properties of zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Muth-Kohne et al [28] reported a decrease in egg yolk sac size following exposure to AgNPs (< 20 nm size) at 48 hpf, using a significantly higher dose of 73 mg/L. It is known that silver can accumulate in tissues both in the form of ions and in the form of nanoparticles [29]. The silver content measurement result in the present study could not ascertain the form of metal inside the tissue, which is one of the drawbacks of using ICP-MS to examine the uptake of nanometals.…”
Section: Discussionmentioning
confidence: 96%
“…[10][11][12] Only recently, some studies have appeared in which different forms of NMs were reported in tissues of organisms, providing insights into form-specific uptake of NMs. [13][14][15][16] Methods to quantify form-specific concentrations of NMs such as single particle inductively coupled plasma mass spectroscopy (sp-ICP-MS) for metal-based NMs are becoming more available. These developments in analytical methods have enabled modelling approaches that could reveal patterns of form-specific uptake and accumulation of NMs in organisms, such as aspects of absorption, distribution, metabolism and excretion (ADME).…”
Section: Introductionmentioning
confidence: 99%